The role of primary care pharmacist in the management of chronic illnesses in young people: a qualitative study. (1st April 2022) - Almunef, M; Mason, J; Curtis, C; Jalal, Z
Abstract: Introduction: Recent evidence has shown that the incidence of long-term illnesses in young people is increasing (1). Pharmacists, as medicine experts, are in a unique position to promote young people's health by improving their knowledge regarding effective use of medication through the provision of pharmaceutical services. To date, there are few studies that have explored the potential roles of primary care pharmacists in providing health care for young people with long term illnesses (2). This study attempts to show the potential role of primary care pharmacists in caring of young people with chronic illnesses. Aim: To explore the role of primary care pharmacists in the management of chronic illnesses in young people aged 18-24 years. Methods: A qualitative study was undertaken. From June to November 2019, semi-structured interviews were conducted with 23 primary care pharmacists in the UK. A purposive sampling strategy was followed to form a population for this study. The targeted participants were UK primary care pharmacists i.e. General Practice (GP) and community based pharmacists. Through professional networks, the participants were identified, approached and recruited by email or in person. Interviews on average lasted 35 minutes, and were audio recorded, transcribed verbatim and analysed inductively using thematic analysis. Emergent themes were reviewed by all authors and any discrepancies were resolved through discussion. Results: Four themes emerged from the data: pharmacists' roles, prescribing issues, pharmaceutical services and young people medication-related experiences. Participants identified several roles for primary care pharmacists in caring of young people with chronic illness. These roles included encouraging young people to visit the pharmacy to collect their medicines and ensuring that they have enough medicines supply, counselling and educating young people about their medicines and answering their queries, building trusted relationships directly with them, provision of specialist services, following up with young people and checking on medication compliance, and signposting them for further support. The most discussed chronic illnesses in young people by participants were respiratory diseases such as asthma and mental health illnesses. However, many pharmacists perceive a fundamental communication barrier that hinders the provision of this support, i.e., lack of access to the patient. Participants identified a lack of support from other health care providers as one of the associated challenges for pharmacists in supporting young people with chronic illness. Conclusion: Primary care pharmacists felt that they have an important role in supporting young people with chronic illness. This study identified many ways in which pharmacists provide services and support to young people. This study makes a major contribution to the limited literature on primary care pharmacists' experience of dealing with young people with chronic illness by exploring the pharmaceutical care currently available and identifying other issues which may influence pharmaceutical care. Although the research was limited by a relatively small number of participants, the findings of this research could inform future research to provide more evidence of the benefit of primary care pharmacists in supporting young people with chronic illness in the optimal use of their medication. References: (1) Shah R, Hagell A, Cheung R. International comparisons of health and wellbeing in adolescence and early adulthood. London (UK): Nuffield Trust; 2019. (2) Gray N, Shaw K, Smith F, et al. The Role of Pharmacists in Caring for Young People With Chronic Illness. Journal of Adolescent Health, 2017; 60 (2): 219–225.